Postoperative Numbness: A Survey of Patients After Hip Arthroscopic Surgery. Issue 5 (4th May 2018) - Reda, Bashar; Wong, Ivan
Background: Hip arthroscopic surgery is a rapidly growing procedure that requires distraction of the leg to access the joint. A frequently reported complication of this procedure is postoperative numbness, with rates between 1% and 20% reported in the literature. Purpose/Hypothesis: The purpose of this study was to determine the factors contributing to the development and effect of numbness on functional outcomes. We hypothesized that this complication is underreported and that its prevalence is higher than what has been described in the literature. Study Design: Case series; Level of evidence, 4. Methods: Patients who had undergone hip arthroscopic surgery between 2012 and 2016 were included, and a telephone survey was conducted to collect data. Data related to the procedure and outcome scores were collected via a systematic chart review for the included patients. Data analysis was conducted for means, SDs, frequencies, and percentages. For comparative statistics, t tests and multiple logistic regression models were used. Results: A total of 221 patients (113 male, 108 female; mean age, 39.8 ± 13.34 years) completed the survey out of 362 eligible patients. Overall, 37% (n = 82) of patients reported having experienced some form of numbness after surgery. Approximately 43% (35/82) of the patients reported resolution by 6 weeks postoperatively, and 68% (56/82) of numbness was reported to have completely resolved by 6 months. The duration of surgery was a significant factor for the development of postoperative numbness ( P = .010; odds ratio, 2.18) when comparing procedures longer than 50 minutes with procedures shorter than 50 minutes (first incision until closure). Postoperative numbness was associated with a negative effect on the International Hip Outcome Tool–33 (iHOT-33) score that reached statistical significance at the 1-year (numbness, 60.19; no numbness, 74.21; P = .006) and 2-year time points (numbness, 52.04; no numbness, 72.69; P = .01). Conclusion: This study confirmed our hypothesis that postoperative numbness is more common in our patient population than the incidence reported in the literature. This adverse event was also shown to be associated with decreased postoperative functional outcomes, as measured by the iHOT-33 at 1 and 2 years postoperatively.